2013
DOI: 10.1016/j.yjmcc.2012.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin receptors and protein quality control

Abstract: Protein quality control (PQC) is essential to intracellular proteostasis and is carried out by sophisticated collaboration between molecular chaperones and targeted protein degradation. The latter is performed by proteasome-mediated degradation, chaperone-mediated autophagy (CMA), and selective macroautophagy, and collectively serve as the final line of defense of PQC. Ubiquitination and subsequently ubiquitin (Ub) receptor proteins (e.g., p62 and Ubiquilins) are important common factors for targeting misfolde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 157 publications
0
69
1
1
Order By: Relevance
“…Previous studies have confirmed that protein ubiquitination serves multiple roles in different biological processes. It is known that ubiquitination is crucial for protein degradation (31). The E2 ubiquitin-conjugating enzyme RAD6 catalyzes target proteins through ubiquitination (22).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed that protein ubiquitination serves multiple roles in different biological processes. It is known that ubiquitination is crucial for protein degradation (31). The E2 ubiquitin-conjugating enzyme RAD6 catalyzes target proteins through ubiquitination (22).…”
Section: Discussionmentioning
confidence: 99%
“…If the proteins cannot be maintained in a soluble state and handled by the first lines of chaper one and UPS defence, selective macroautophagy can occur 8,45 . In macroautophagy, a portion of the cytoplasm containing damaged organelles and aberrant proteins are engulfed in a membrane bound compartment for degradation by lysosomes, after which the amino acids and fatty acids are recycled into ATP 46 .…”
Section: The Proteostasis Network Componentsmentioning
confidence: 99%
“…The immunoproteasome in non-immune cells can be induced by viral infection and γ-interferon and is presumably more suitable for generation of peptide fragments for antigen presentation [21]. In UPS-mediated protein degradation, ubiquitination and proteasomal degradation of a substrate is coupled via intra- and extra- proteasomal Ub receptors (Figure 2) [22]. …”
Section: Ups Dysfunction In Cardiac Proteotoxicitymentioning
confidence: 99%